Glacier fluctuations of Muztagh Ata and temperature changes during the late Holocene in westernmost Tibetan Plateau, based on glaciolacustrine sediment records. Issue 17 (11th September 2014) - Liu, Xingqi; Herzschuh, Ulrike; Wang, Yongbo; Kuhn, Gerhard; Yu, Zhitong
Abstract Late Holocene glacier variations in westernmost Tibetan Plateau were studied based on the analysis of grain size, magnetic susceptibility, and elements from an 8.3 m long distal glaciolacustrine sediment core of Kalakuli Lake. Our results show that there are four glacier expansion episodes occurring in 4200–3700 calibrated years (cal years) B.P., 2950–2300 cal years B.P., 1700–1070 cal years B.P., and 570–100 cal years B.P. and four glacier retreat periods of 3700–2950 cal years B.P., 2300–1700 cal years B.P., 1070–570 cal years B.P., and 50 cal years B.P.–present. The four glacier expansion episodes are generally in agreement with the glacier activities indicted by the moraines at Muztagh Ata and Kongur Shan, as well as with the late Holocene ice‐rafting events in the North Atlantic. Over the last 2000 years, our reconstructed glacier variations are in temporal agreement with reconstructed temperature from China and the Northern Hemisphere, indicating that glacier variations at centennial time scales are very sensitive to temperature in western Tibetan Plateau.